The power generation sector's demand for fossil fuels: a quantitative assessment on the viability of carbon fees for the reduction of greenhouse gas emissions. (1st January 2002) - Seres, Stephen; Thomassin, Paul J.
The demand for fossil fuels by Ontario's conventional steam power generation sector is examined in this paper. It is hypothesised that the enactment of a carbon fee policy will induce a change in the relative prices of the three fuels used in this sector (coal, natural gas and heavy fuel oil). This would lead to substantial interfuel substitution and greenhouse gas abatement. The demand share equations for the three fuels are derived from the translog functional form and set in a simulation model to estimate the value of a carbon fee necessary, to reduce carbon dioxide emissions in compliance with the Kyoto Protocol. Results suggest that a fuel specific carbon fee policy would be successful in achieving the desired emissions reduction at a negligible net cost to society.